Penerapan Ice Breaking Dan Implikasinya Terhadap Motivasi dan Minat Belajar Pada Mata Pelajaran PAI di SDIT Khoiru Ummah - Watia, Larasi; Warsah, Idi; Amrullah (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the implementation of ice breaking activities and their implications for students’ motivation and interest in learning Islamic Religious Education at SDIT Khoiru Ummah. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that students showed low enthusiasm and interest in PAI lessons, especially during less favorable time slots. Ice breaking activities were implemented at the beginning, during, and end of lessons to create a more engaging and positive learning atmosphere. These activities, both spontaneous and planned, helped boost students’ motivation, concentration, social interaction, and active participation. The study concludes that well-integrated ice breaking techniques can significantly enhance students’ learning motivation and interest in PAI, leading to a more dynamic and effective classroom environment.